Coleophora cantabrica Baldizzone, sp. nov. a new species from Spain. Coleophora repentis Klimesch, 1947 new species for the Iberian Peninsula. Contribution to the knowledge of Coleophoridae CLVI (Lepidoptera: Coleophoridae) - Giorgio Baldizzone (SHILAP)
The publication deals with the description of Coleophora cantabrica Baldizzone, sp. nov., species of the Cantabrian Mountains and Sierra de Gredos belonging to the group of C. genistae Stainton, 1857, close to C. oreiosella Baldizzone, 2019. C. repentis Klimesch, 1947 is also reported, for the first time from Spain and the Iberian Peninsula.